Reassignment of a junior synonym of Lepisosteus oculatus Winchell 1864 to L. platostomus Rafinesque 1820 - Sinopoli, Daniel; Near, Thomas J.; David, Solomon R.; Chakrabarty, Prosanta (Zootaxa, 2024)
N/A